PERALIHAN HAK MILIK ATAS TANAH MELALUI PEWARISAN DI DESA WAWONGGURA KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Rahman Hasima; Heryanti Heryanti; Fitriah Faisal; Muh. Nazar; Zahrowati Zahrowati; Jabalnur Jabalnur; Endah Widyastuti (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
The purpose of this service activity is to increase the community's legal knowledge and understanding of the transfer of land ownership rights through inheritance in Wawonggura Village, Palangga District, South Konawe Regency. The stages of activities to be carried out are as follows: (a) the preparation stage includes: survey; stabilization and determination of locations and objectives; preparation of training materials, which include: impression materials, PowerPoint slides, (b) The implementation stage includes: (1) Explanation of material on the transfer of ownership rights to land through inheritance. This session also focused on providing an explanation of the mechanism for transferring ownership rights to land through inheritance, (2) legal counseling on the transfer of ownership rights to land through inheritance carried out by a community service team from universities involving students. The methods used during the process of community service activities include (a) lecture method to provide direct explanation to the community (b) question and answer method to explore public knowledge of the material provided. The result achieved in this service activity is the increase in knowledge and understanding of the law of the people of Wawonggura Village regarding the transfer of ownership rights to land through inheritance. This is aimed at increasing knowledge and understanding of community law before and after community service activities are carried out through legal counseling, namely 50% for understanding the transfer of ownership rights to land and inheritance and 45% for understanding the procedure for transferring ownership rights to land through inheritance.